A fatal grace [compact disc, unabridged] - Penny, Louise (Penny, Louise. Three Pines mystery, 2007)
They are known as Team Midnight, an elite force trained to disappear behind enemy lines, to wreak havoc where an enemy least expects it. Their job is simple-hide in the shadows, kill without hestitation, and complete the mission at all costs.